The synergy of neuromarketing and artificial intelligence: A comprehensive literature review in the last decade - Ahmed H. Alsharif; Junhai Wang; Salmi Mohd Isa; Nor Zafir Md Salleh; Husam Azzawi Dawas; Mohammed H. Alsharif (Future Business Journal)
Abstract This paper conducts a systematic literature analysis on "artificial intelligence, ethical artificial intelligence, neuromarketing, consumer neuroscience, neuroethics, and neurotechnology." This study followed the systematic literature review methodology to select and extract the relevant documents from the Scopus database (2013–2023). The findings revealed the valuable transformative impact of integrating artificial intelligence (AI) into neuromarketing (NM) and consumer neuroscience (Cons-Neuro), redefining the understanding and influence of consumer behavior. Emotion, attention, and memory have become vital in NM and AI studies. AI algorithms analyze vast neural and physiological datasets, offering marketers insights into the emotional impact of campaigns, granular insights into consumer focus, and optimizing content for maximum impact. Furthermore, memory plays a vital role in increasing brand recall and fostering lasting relationships. In addition, integrating brain-computer interfaces (BCI) into consumer neuroscience provides direct insights, with AI interpreting BCI data for real-time adjustments. The synergy of NM and AI offers insights into consumer behavior's cognitive and emotional aspects. While enabling targeted campaigns and improved customer experiences, this integration raises ethical concerns necessitating transparency and responsible neural data use. This paper offers valuable insights into the intersection of AI and NM, exploring innovative applications and ethical considerations in these evolving fields.